Sago Palm 2018
DOI: 10.1007/978-981-10-5269-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Acid Modification of Sago Hampas for Industrial Purposes

Abstract: Sago pith and sago hampas mainly consist of starch and fiber. In this research, acid modification of starch and fiber was conducted by high-temperature (autoclaving) and microwave-assisted treatments and slow or mild acid hydrolysis. Autoclaving and microwave-assisted treatments influenced the gelatinization and solubilization of starch granules to produce depolymerized starch and changed the fiber structure to become more amorphous forms. Heating in dilute acid produced high soluble total sugars with high dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…From the results, extractive free components of RSH (organic and inorganic components) was found to be 9.89% which is in line with the <10% quoted by Yang and Jaakkola, [28]. However, the study also reported 11.57% lignin in RCH which corroborates with the study by Utami et al, [29] with the percentage lignin in sago hampas at 12%.…”
Section: Physico-chemical Parameterssupporting
confidence: 90%
“…From the results, extractive free components of RSH (organic and inorganic components) was found to be 9.89% which is in line with the <10% quoted by Yang and Jaakkola, [28]. However, the study also reported 11.57% lignin in RCH which corroborates with the study by Utami et al, [29] with the percentage lignin in sago hampas at 12%.…”
Section: Physico-chemical Parameterssupporting
confidence: 90%
“…Pichia , the dominant non-Saccharomyces fungal genus in the fermented grains of the Guizhou region, not only decomposes lactic acid to maintain vigorous growth under acid stress but also inhibits the growth of filamentous fungi and Bacillus by producing toxins and organic acids [ 28 , 29 , 32 , 33 , 34 ]. Issatchenkia can thrive in varied fermentation environments, owing to its high acid and temperature tolerance, while producing various acids and ethanol to shape the microbial community structure [ 35 , 36 ]. The acidity of fermented grains was positively correlated with the relative abundance of Issatchenkia and Pichia ( Figure 5 D), indicating that acidity had a remarkable driving effect on the microbial community succession during the third round of fermentation of sauce-flavor baijiu in the Beijing region.…”
Section: Discussionmentioning
confidence: 99%
“…Pichia, the dominant non-Saccharomyces fungal genus in the fermented grains of the Guizhou region, not only decomposes lactic acid to maintain vigorous growth under acid stress but also inhibits the growth of filamentous fungi and Bacillus by producing toxins and organic acids [28,29,[32][33][34]. Issatchenkia can thrive in varied fermentation environments, owing to its high acid and temperature tolerance, while producing various acids and ethanol to shape the microbial community structure [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Plus, kojic acid is a non-toxic natural product deliberating admirable biodegradability and tyrosinase (catalyzing enzyme for melanin production) inhibition properties. 33 Kojic acid is prepared by fermentation of sago biomass 34 while azobenzene is obtained from the esterification process. 35 Commonly, the chemical and thermal reduction methods are applied in the production of rGO.…”
Section: Introductionmentioning
confidence: 99%